2019
DOI: 10.1111/jpn.13226
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of dietary supplementation of three probiotics on milk yield, milk composition and intestinal flora in Sannan dairy goats varied in kind of probiotics

Abstract: In this study, we investigated the effects of Saccharomyces cerevisiae (SC), Bacillus subtilis (BS) and Enterococcus faecalis (EF), singly and in combination, on the dry matter intake (DMI), milk production and composition, and faecal microflora of Saanen dairy goats. Fifty goats were randomly divided into five groups: (a) basal diet (control);(b) basal diet + SC; (c) basal diet + BS; (d) basal diet + EF; and (e) basal diet + mixed probiotics. Each treated animal received 5 g/d of probiotics for a total admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 50 publications
6
21
0
2
Order By: Relevance
“…A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27]. Our research indicated that the Firmicutes abundance in the rumen and caecum increased after feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09, but the Bacteroidetes abundance decreased in rumen and caecum, indicating that Bacillus amyloliquefaciens fsznc-06 and Bacillus pumilus fsznc-09 improved Firmicutes proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…A good digestive tract microbiota benefits the host by regulation of the physiological procedure and mucosal immunity, from producing antimicrobial substances to suppressing the proliferation of digestive tract pathogens [23], leading to a highly efficient rumen function [24] and improving growth performance through improving the digestive tract microbial ecosystem [25]. In the present study, Firmicutes and Bacteroidetes were the two dominant phyla in the rumen and caecum, which is in agreement with previous studies [26,27]. Our research indicated that the Firmicutes abundance in the rumen and caecum increased after feeding weanling goats with Bacillus amyloliquefaciens fsznc-06 or Bacillus pumilus fsznc-09, but the Bacteroidetes abundance decreased in rumen and caecum, indicating that Bacillus amyloliquefaciens fsznc-06 and Bacillus pumilus fsznc-09 improved Firmicutes proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…And, Hern andez-Coronado et al (2019) also reported that EO at 400 mg/L can serve as natural alternative additives in drinking water to improve broiler production and meat quality. Besides, there have been a number of studies about the use of BS or EO on piglet (Tian and Piao 2019), aquaculture (Jiang et al 2019), beef (Alemu et al 2019), and goat (Ma et al 2020). Therefore, BS and EO are receiving increasing attention as potential antibiotic growth promotor alternatives and are already employed in many commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Since high SCC and milk of inferior are the common indicator and consequence of mastitis for dairy cows, decreased SCC and improved milk quality in our study suggested the amelioration of mastitis. Higher milk percentage of fat and lactose caused by dietary supplementation of yeast has been reported in dairy goats (Ma et al 2019) and dairy cows (Olagaray et al 2019), while similar study with LAB are rare. Catozzi et al (2019) reported that intramammary incubation of inactivated Lactobacillus rhamnosus caused significant increase of SCC on cows with subclinical at the beginning but decreased afterwards, as well as modulation of milk microbiota.…”
Section: Discussionmentioning
confidence: 72%